Preparation of CNTs/PP@Gr composites with a segregated structure and enhanced electrical and thermal conductive properties by the Pickering emulsion method. (3rd May 2022) - Hu, Shengfei; Xu, Bingfeng; Zhao, Yang; Fu, Xudong; Liu, Qingting; Zhang, Rong
Abstract: Conductive and thermal conductive polymer composites have significant advantages in corrosion resistance and mechanical and processing properties. To improve the integrity of the network structure of the conductive filler in a polypropylene (PP) matrix, PP@Graphite (Gr) with segregated single-network structure, PP@(carbon nanotubes (CNTs)/Gr) with segregated double-network structure, and (x wt%-CNTs/PP)@Gr with segregated hybrid double-network structure were prepared by the Pickering emulsion method. The original irregular powder was converted into spherical shape by the Pickering emulsion method. Among these composites, the (2 wt%-CNTs/PP)@Gr composite had the highest conductivity and thermal conductivity. The electrical and thermal conductivity of the (2 wt%-CNTs/PP)@Gr composite reached 1.45 S/m and 0.82 W/m·K, respectively, at a Gr loading of 13.01 wt%, and the electrical conductivity was 3 and 0.5 times higher than that of PP@Gr and PP@(CNTs/Gr) composites, respectively. The CNTs acted as "bridges" to form a denser conductive network, and significantly improved the conductivity. The interfacial thermal resistance of the (2 wt%-CNTs/PP)@Gr composite was between 1.5 × 10-7 and 1 × 10-6 m2K/W according to the effective medium theory (EMT) fitting results. Additionally, the crystalline peaks of the PP@Gr and PP@(CNTs/Gr) composites showed a significant left shift, while the (2%-CNT/PP)@Gr composite showed a significant right shift, which indicated that the hybridization of CNTs with Gr caused a "bridge effect" and increased the thermal conductivity. This method provides a convenient and time-saving new approach for the study of segregated structural thermally conductive composites by encapsulating the filler on the matrix through a one-step process while meeting the requirements of green environment. Graphical abstract: Image 1